Sequential Navigated Multilocus Repetitive Transcranial Magnetic Stimulation for Concurrent Somatic and Psychiatric Conditions - Jääskeläinen, Satu K.; Tram, Mi; Taiminen, Tero (Lippincott, Williams & Wilkins, 2025)
Objective: Repetitive transcranial magnetic stimulation (rTMS) is efficient in frequently coexisting neurological and psychiatric disorders. This retrospective study investigated potentially additive efficacy and feasibility of multilocus rTMS in patients treated for more than 1 concurrent disorder.
Methods: Thirty-three consecutive patients underwent therapeutic rTMS with several cortical targets for more than 1 disorder. Two patients were excluded (insufficient data). The patients (19 women and 12 men, median age 49 years, range 17–75 years) had combinations of chronic pain (n = 15), depression (n = 30), tinnitus (n = 7), anxiety (n = 6), obsessive-compulsive disorder (n = 3), and eating disorder (n = 3). The combination of pain and depression was most frequent. E-field navigated TMS device (Nexstim Ltd, Helsinki, Finland) was used for a 10-day rTMS-trial (9 in 2 cases). Protocol and cortical target combinations varied according to indications. In addition to clinical evaluation, at least 30% decrease in severity on disorder-specific scales was response limit. All assessments were done at baseline and after 10-day treatment.
Results: Response rate to multilocus rTMS in at least 1 condition was 84%. A response to treatment was observed for both indications in 19 patients, for a single indication in 7 patients, and for none in 5 patients. As available (n = 20), Global Impression of Change was positive in 85% of patients, and 15% reported no change.
Conclusions: Multilocus rTMS is an efficient tool for comorbid neurological and psychiatric disorders, with no serious adverse effects. Responder rate was rather high in patients with comorbidities, suggesting that rTMS efficacy may be associated with inherent patient-related factors.